Role of rhamnolipids in Pseudomonas aeruginosa RW9 remediation of hexavalent chromium - Mat Arisah, Fatini (2023)
Chromium hexavalent (Cr(VI)) pollution has become a global issue. Despite the efficiency of various bacterial species reported to treat the pollutant, the removal performance of each species and strains were found to be distinctive. The same phenomenon was also observed in Pseudomonas aeruginosa as a well-known efficient species in Cr(VI) remediation. The discrepancy in performance might be resulted from the removal mechanisms deployed by the strains. Thus, in this study the potential of P. aeruginosa RW9 in Cr(VI) remediation was assessed. The strain was subjected to a range of Cr(VI) to evaluate its tolerance. Results showed its ability to resist a high concentration of up to 40 mg/L Cr(VI). The Cr(VI) distribution analysis by a shake flask study at 30 °C, agitation of 150 rpm for 24 hours incubation with 10 mg/L Cr(VI) was conducted. It was revealed that the strain developed a complex mechanism to remove Cr(VI), based on surfacebound (0.46 mg/L), intracellularly accumulated (1.24 mg/L) and extracellular sequestration (6.74 mg/L), which accounted for approximately 85% of the removal efficiency. The extracellular sequestration was attributed to the extracellular reductase and biosurfactant with the latter discovered as the predominant metabolite. High performance liquid chromatography with a variable wavelength detector (HPLC-VW) revealed that the strain produced more biosurfactant in Cr(VI) treated experiment as compared to that of the control (0 mg/L Cr(VI)). The biosurfactant was extracted by acid precipitation coupled with ethyl acetate extraction and purified by using solid phase extraction method prior to characterisation analyses by fourier transform infra-red spectroscopy, nuclear magnetic resonance (NMR) and liquid chromatography mass spectrometry (LCMS) analyses to confirm the rhamnolipid structure. The LC-MS analysis also exposed that cells in both control and Cr(VI) treated experiments produced more di-rhamnolipid with the main congener being Rha-Rha-C10-C10 (m/z 649). Furthermore, Cr(VI) was found to induce the synthesis of Rha-Rha-C8-C10/ Rha-Rha-C10-C8 congener (m/z 620). The Whole Genome Sequencing (WGS) verified the presence of the rhamnolipid-encoded genes (rhlA, rhlB and rhlC) and reductase-encoded gene (chrR) before conducting the one-step quantitative reverse transcriptase polymerase chain reaction (qRT-PCR). It was discovered that Cr(VI) induced the transcriptional expression of all the target genes with the highest enhancement observed in rhlB. Later, the performance of the produced rhamnolipid was tested to assess its efficiency to remediate six chosen elements (Se, Cd, B, Cr, Zn and Mn) in partially treated leachate considering the metals concentration in the wastewater. The rhamnolipid, in its crude form of 10 mg/L, was applied to the wastewater and the remaining concentrations of the elements were measured using inductively coupled plasma atomic emission spectroscopy (ICP-OES). Se and Cd were completely removed after a 48-hour treatment. Meanwhile, B, Zn, Cr and Mn were reduced at 93.45%, 77.37%, 68.04% and 55.42%, respectively. The rhamnolipid exhibited preferential to the respective elements following Se > Cd > B > Cr > Zn > Mn sequence. The same pattern was also displayed by the commercial rhamnolipid which served as the control experiment. Collectively, the findings proved that the strain has a great potential for application in Cr(VI) bioremediation. In terms of application, it can be manipulated to produce rhamnolipid which exhibited various downstream applications especially in remediating metal pollutants.